The Idiomatic Value of the Stressed Object in Arabic Language Structures - Al-Ghanimi, Dr. Sabah Daier (International Journal of Psychosocial Rehabilitation, 2020)
This Research deals with the idiomatic value of the stressed Object in Arabic language structures. It clarifies the various Types of The Stressed object which includes or repeats the meaning of preceding verb or context. The Research draw he significance of the idiomatic value of the stressed object from The Qur’anic verses structures, Arabic poetry and EloQuent texts in order to help students and faculty members in Their study of Arabic language and to present an easy to reach information about This important area of interest.